Development of a web-based waste bank information system using the waterfall method - Aditiya, Moh Vicri; Prakasa, Gustav Ernest; Kristiyanto, Yogi; Sarah, Siti; Muzaeni, Amin; Susanto, Yodi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Waste management issues in Indonesia, particularly household waste which contributes 38.2% of the total national waste, demand a more systematic approach through waste banks. However, current waste bank operations are still dominated by manual recording, which is susceptible to human error, data loss, and inefficiency in generating periodic reports for the Environmental Office (DLH). This study aims to develop a Web-Based Waste Bank Information System to optimize customer data management, transaction accuracy, and financial report integration. The research methodology employed is Research and Development (R&D) using the Waterfall development model, which includes stages of requirements analysis, system design, implementation, and testing. The research population involves waste bank administrators and customers as the primary subjects for operational trials. The results are expected to produce a digital platform capable of enhancing customer balance transparency, minimizing data entry errors, and accelerating administrative reporting processes, thereby supporting more efficient urban environmental governance.